2019
DOI: 10.18326/muqtasid.v10i1.57-68
|View full text |Cite
|
Sign up to set email alerts
|

Revitalisasi Pendistribusian Zakat Produktif Sebagai Upaya Pengentasan Kemiskinan di Era Modern

Abstract: The purpose of this study was to determine the distribution of productive zakat in the form of venture capital carried out by BAZNAS (National Zakat Agency) as an effort to alleviate poverty in the city of Yogyakarta. The type of research is field research. The research method is qualitative descriptive. The results of the study revealed that the implementation of productive zakat capital had a positive impact on alleviating poverty, increasing income and bring forth new entrepreneurs. Therefore, the program o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 2 publications
2
11
0
11
Order By: Relevance
“…Studies dealing with the distribution of zakat in a productive way include Haidir (2019) who questions whether providing venture capital by BAZNAS could lessen poverty in Yogyakarta City and found that it did reduce poverty, increase income and give birth to new entrepreneurs. Wiradifa & Saharuddin (2018) found zakat distribution in BAZNAS South Tangerang City in three forms: traditional consumptive, traditional productive, and creative productive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies dealing with the distribution of zakat in a productive way include Haidir (2019) who questions whether providing venture capital by BAZNAS could lessen poverty in Yogyakarta City and found that it did reduce poverty, increase income and give birth to new entrepreneurs. Wiradifa & Saharuddin (2018) found zakat distribution in BAZNAS South Tangerang City in three forms: traditional consumptive, traditional productive, and creative productive.…”
Section: Introductionmentioning
confidence: 99%
“…It has a positive effect on mustahiq income to improve their standard of living. zakat productive program has been able to create a jobs for the other mustahiq, and has been able to create mustahiq who has high creativity and competitiveness (Haidir, 2019;Naimah and Soenjoto, 2018). Romdhoni (2018) found too that Income affects the improvement of the welfare of the poor in Sragen during rhis zakat productive program.…”
Section: Discussionmentioning
confidence: 99%
“…Dalam rangka pendistibusian zakat yang dilakukan oleh penyalur dalam hal ini Baznas mesti tepat sasaran agat tidak salah dalam penggunaannya karena zakat yang diberikan tujuannya adalah untuk membantu masyarakat yang tidak mampu. Semakin banyak zakat yang terkumpul semakin tepat sasaran pula dalam pendistribusiannya maka akan semakin mampu untuk mengurangi kemiskinan ada dimasyarakat (Haidir 2019)…”
Section: Tepat Sasaranunclassified